Multi-effect flame-retardant in-situ gel polymer electrolyte and application thereof

By constructing a multi-effect flame-retardant in situ gel polymer electrolyte in lithium-ion battery electrolyte, the synergistic effect of phosphorus and fluorine is used to solve the problem of insufficient flame retardant performance of the battery electrolyte, and higher battery safety and electrochemical performance are achieved.

CN120127206APending Publication Date: 2025-06-10HU ZHOU YAO NING GU TAI DIAN CHI YAN JIU YUAN YOU XIAN GONG SI

Patent Information

Application Number
CN202510163656.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The flame retardant performance of existing lithium-ion battery electrolytes is insufficient, and it is prone to leakage, combustion or explosion under extreme conditions, affecting the safety of the battery.

Method used

A multi-effect flame-retardant in situ gel polymer electrolyte is used. This electrolyte significantly improves the flame retardant effect of the electrolyte by building a flame retardant on a three-dimensional network framework and leveraging the synergistic effect of phosphorus and fluorine.

Benefits of technology

While not sacrificing electrochemical properties, the flame retardant performance of lithium-ion batteries is significantly improved, the decomposition of flame retardant is inhibited, and the mechanical strength and safety of the batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a multi-effect flame-retardant in-situ gel polymer electrolyte and application thereof. The electrolyte is a gel polymer electrolyte with a three-dimensional network structure prepared from a first flame retardant, a second flame retardant, a cross-linking agent, an initiator and a liquid electrolyte in situ, the first flame retardant is an acrylate liquid-phase monomer containing a phosphorus element, and the content of the first flame retardant accounts for 1-4wt% of the total mass of the electrolyte; the second flame retardant is an acrylate liquid-phase monomer containing a fluorine element, and the content of the second flame retardant accounts for 1-4wt% of the total mass of the electrolyte; the content of the cross-linking agent accounts for 1-2wt% of the total mass of the electrolyte; the content of the initiator accounts for 0.05-1wt% of the total mass of the electrolyte; and the balance is liquid electrolyte. According to the invention, the flame retardant is effectively constructed on a three-dimensional network skeleton, so that the flame-retardant effect of the gel polymer electrolyte is enhanced under the synergistic effect of phosphorus and fluorine while the electrochemical performance is not sacrificed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion battery materials, and particularly relates to a multi-effect flame-retardant in-situ gel polymer electrolyte and its application. Background Art

[0002] Lithium-ion batteries (LIBs) have been widely used in fields such as electric vehicles, mobile devices, and large-scale energy storage power stations due to their high energy density and long cycle life. However, with the continuous expansion of application scenarios, the safety issues of batteries have become increasingly prominent, especially the safety of the electrolyte has become one of the key factors restricting the further development of lithium-ion batteries.

[0003] Traditional lithium-ion battery electrolytes usually use carbonate solvents such as ethylene carbonate (EC) and dimethyl carbonate (DMC). Although such solvents have high ionic conductivity and good electrochemical stability, their low flash point and high flammability make the battery prone to leakage, combustion, or even explosion under extreme conditions (such as overcharging, short-circuiting, or high temperature), seriously threatening the life and property safety of users. Therefore, developing flame-retardant or non-flammable electrolytes with high safety has become an important research direction for current lithium-ion batteries.

[0004] At present, researchers have proposed a variety of strategies to improve the safety of electrolytes, mainly including the following: (1) Adding flame retardant additives: By introducing flame retardants (such as phosphate compounds) into the electrolyte to inhibit the flammability of the electrolyte. However, although such additives can effectively improve the flame retardancy of the electrolyte, their compatibility with electrode materials is poor and they are prone to decomposition during charge and discharge, affecting the electrochemical performance of the battery. (2) Using flame retardant solvents or co-solvents: Using solvents with flame retardant properties (such as fluorinated carbonates, phosphate solvents) to replace part or all of the traditional carbonate solvents. Although such solvents can reduce the flammability of the electrolyte, their ionic conductivity and electrochemical stability are usually poor, limiting their application in actual batteries. (3) High-concentration electrolytes: By increasing the concentration of lithium salts to reduce the flammability of the electrolyte. Although high-concentration electrolytes can improve the safety of the battery, their cost is high and their viscosity is large, resulting in a decrease in ionic conductivity and still need to be further optimized in practical applications. (4) Ionic liquids: Ionic liquids have extremely low flammability and high thermal stability and are considered ideal flame retardant electrolytes. However, the high cost and poor low-temperature performance of ionic liquids limit their large-scale application. (5) Gel polymer electrolytes (GPE): GPE combines the advantages of solid electrolytes and liquid electrolytes. By fixing the liquid electrolyte in the polymer matrix, the leakage problem of the electrolyte is avoided, thereby improving the safety of the battery. However, traditional GPE usually uses linear polymers, which have poor mechanical strength and low network formation efficiency, resulting in limited solvent absorption of GPE. In addition, GPE cannot completely prevent the volatilization of the internal electrolyte, and part of the electrolyte will still volatilize and thermally decompose into flammable vapors when heated, posing a certain safety hazard. To further improve the flame retardancy of GPE, researchers have tried to directly add flame retardants to commercial electrolytes or fix flame retardants in the polymer matrix. However, the electrochemical stability of phosphorus-containing flame retardants is poor and they are prone to decomposition on the surface of the negative electrode during battery charge and discharge, affecting the performance of the battery. In addition, only when the content of the flame retardant is very high, the flame retardant effect of GPE is more obvious, but this will significantly reduce the electrochemical performance of the battery.

[0005] In summary, although the prior art has improved the safety of lithium-ion battery electrolytes to a certain extent, there are still many problems, such as poor compatibility between flame retardants and electrode materials, cost and viscosity problems of high-concentration electrolytes, insufficient mechanical strength and flame retardancy of GPE, etc. Therefore, developing a new electrolyte system that can effectively improve the flame retardancy of the electrolyte without significantly affecting the electrochemical performance of the battery has important practical significance and application value. Summary of the Invention

[0006] Aiming at the deficiencies of the prior art, the present invention provides a multi-effect flame-retardant in-situ gel polymer electrolyte and its application. By effectively constructing the flame retardant on the three-dimensional network skeleton, while not sacrificing the electrochemical performance, the flame-retardant effect of the gel polymer electrolyte is enhanced under the synergistic action of phosphorus and fluorine, providing a new solution for the development of high-safety and high-performance lithium-ion batteries.

[0007] The present invention is realized through the following technical solutions:

[0008] A multi-effect flame-retardant in-situ gel polymer electrolyte, wherein the electrolyte is a gel polymer electrolyte with a three-dimensional network structure prepared in-situ from a first flame retardant, a second flame retardant, a cross-linking agent, an initiator and a liquid electrolyte; the first flame retardant is a liquid-phase monomer of acrylate containing phosphorus element, and its content accounts for 1-4 wt% of the total mass of the electrolyte; the second flame retardant is a liquid-phase monomer of acrylate containing fluorine element, and its content accounts for 1-4 wt% of the total mass of the electrolyte; the content of the cross-linking agent accounts for 1-2 wt% of the total mass of the electrolyte; the content of the initiator accounts for 0.05-1 wt% of the total mass of the electrolyte; the balance is the liquid electrolyte.

[0009] Preferably, the structural general formula of the monomer of the first flame retardant is as shown in Formula I below:

[0010]

[0011] In Formula I: R 1 , R 2 are each independently selected from alkoxy groups of C 1 -C 4 , heterocyclic alkoxy groups of C 2 -C 6 containing at least one oxygen atom as a ring-forming atom, phenyl, alkanoyl groups of C 1 -C 4 , nitro groups, methylsulfonyl groups, sulfonic acid groups of C 1 -C 4 and alkyl groups of C 1 -C 4 of one kind.

[0012] Preferably, the structural general formula of the monomer of the second flame retardant is as shown in Formula II below:

[0013]

[0014] In Formula II: R 3 , R 4 are each independently selected from -F, -OH, -CF 3 , alkoxy groups of C 1 -C 4 containing at least one oxygen atom as a ring-forming atom, C2 -C 6 in the heterocyclic alkoxy group, phenyl group and C 1 -C 4 in the alkyl group.

[0015] Preferably, the crosslinking agent is a liquid-phase monomer containing one or more acrylate functional groups, and its structural general formula is shown as the following formula III:

[0016]

[0017] In formula III: R 5 , R 6 , R 7 are each independently selected from -OH, -C 3 H 3 O 2 , C 1 -C 4 in the alkoxy group, C 2 -C 6 in the heterocyclic alkoxy group containing at least one oxygen atom as a ring-forming atom, phenyl group, nitro group and methylsulfonyl group.

[0018] Preferably, the initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, dimethyl azobisisobutyrate, 2,2-azobisisobutyronitrile, ammonium persulfate-sodium bisulfite.

[0019] Preferably, the liquid electrolyte includes a solvent and a lithium salt; the solvent is a combination of one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, vinylene carbonate, fluoroethylene carbonate, ethylene sulfate, propylene carbonate, propane sultone, tris(trimethylsilyl) phosphate; the lithium salt is one or more of lithium perchlorate, lithium tetrafluoroborate, lithium difluorophosphate, lithium hexafluorophosphate, lithium difluorooxalate borate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide.

[0020] Application of the above multi-effect flame-retardant in-situ gel polymer electrolyte in the preparation of lithium-ion batteries.

[0021] Preferably, the preparation method of the lithium-ion battery includes the following steps:

[0022] Step 1) Under an inert gas atmosphere, the first flame retardant, crosslinking agent, initiator and liquid electrolyte are fully mixed in proportion to obtain electrolyte precursor A;

[0023] Step 2) Under an inert gas atmosphere, the second flame retardant, crosslinking agent, initiator and liquid electrolyte are fully mixed in proportion to obtain electrolyte precursor B;

[0024] Step 3) Prepare a dry battery cell;

[0025] Step 4) Inject electrolyte precursor B into the dry battery cell. After the electrolyte precursor B is evenly infiltrated, formation and aging are carried out.

[0026] Step 5) Inject electrolyte precursor A into the battery cell processed in Step 4). After standing evenly, high-temperature polymerization is carried out to obtain a flame-retardant gel polymer battery.

[0027] Preferably, the temperature of the formation in Step 4) is 45 - 60 °C, and the current of the formation is 0.05C - 0.2C; the temperature of the aging is 45 - 60 °C, and the time is 24 - 48 h.

[0028] Preferably, the temperature of the high-temperature polymerization in Step 5) is 60 - 80 °C, and the time is 4 - 8 h.

[0029] The beneficial effects of the present invention are as follows:

[0030] (1) Excellent flame-retardant performance: In the present invention, the flame retardant is fixed on the polymer chain through chemical bonds, avoiding the decomposition problem caused by the direct contact between the traditional flame retardant and the electrode material. At the same time, the synergistic effect of the phosphorus- and fluorine-containing double flame retardants significantly improves the flame-retardant effect of the GPE. Among them, the phosphorus-based flame retardant plays a flame-retardant role in the solid phase, while the F free radicals released by the fluorine-based flame retardant during combustion can volatilize into the gas phase to scavenge H free radicals and inhibit the chain combustion reaction, thus achieving a double flame-retardant effect in the gas phase and solid phase.

[0031] (2) Inhibiting the decomposition of the phosphorus-containing flame retardant: In the present invention, by fixing the phosphorus-based flame retardant in the polymer matrix, its direct contact with the electrode material is avoided, effectively inhibiting the decomposition of the phosphorus-containing flame retardant during charge and discharge, and improving the electrochemical stability of the GPE.

[0032] (3) Improving mechanical strength and safety: In the present invention, the flame retardant is fixed in the polymer matrix through chemical bonds to form a three-dimensional network skeleton structure, significantly improving the mechanical strength of the GPE and solving the problems of poor mechanical strength and low network formation efficiency of traditional linear polymers. At the same time, the three-dimensional network structure effectively inhibits the volatilization and leakage of the electrolyte, having a safety advantage compared with traditional GPE.

[0033] (4) Improving electrochemical performance: In the electrolyte of the present invention, the introduction of fluorine element not only enhances the flame-retardant effect, but also is beneficial to the dissociation of lithium salt, increasing the lithium ion transference number of the polymer electrolyte, so that the GPE has good ionic conductivity and electrochemical performance while maintaining excellent flame-retardant performance.

[0034] (5) Reducing the amount of flame retardant: Through the synergistic effect of the phosphorus- and fluorine-containing double flame retardants, the present invention can achieve excellent flame retardant effects at a relatively low flame retardant content, avoiding the problem of the decline in electrochemical performance caused by a high flame retardant content in traditional GPEs.

[0035] (6) Superior comprehensive performance: The present invention is significantly superior to traditional GPEs in terms of flame retardant performance, battery internal resistance, cycle performance, and safety performance. At the same time, the present invention fixes the electrolyte through a three-dimensional network structure, further enhancing the intrinsic safety of the battery. Specific embodiments

[0036] The following further elaborates on the present invention with reference to specific embodiments.

[0037] Unless otherwise specified, the technical means used in the following embodiments are all conventional means well-known to those skilled in the art. The experimental methods without specific conditions indicated are all conventional methods in the art.

[0038] The materials, reagents, etc. used in the following embodiments can all be obtained from commercial sources unless otherwise specified.

[0039] A multi-effect flame retardant in-situ gel polymer electrolyte is a gel polymer electrolyte with a three-dimensional network structure prepared in-situ from a first flame retardant, a second flame retardant, a cross-linking agent, an initiator, and a liquid electrolyte.

[0040] The first flame retardant is a liquid-phase monomer of acrylate containing phosphorus element, and its content accounts for 1-4 wt% of the total mass of the electrolyte. The structural general formula of the monomer is shown as Formula I below:

[0041]

[0042] In Formula I: R 1 , R 2 are each independently selected from an alkoxy group of C 1 -C 4 , a heterocyclic alkoxy group of C 2 -C 6 containing at least one oxygen atom as a ring-forming atom, a phenyl group, an alkanoyl group of C 1 -C 4 , a nitro group, a methylsulfonyl group, a sulfonic acid group of C 1 -C 4 , and an alkyl group of C 1 -C 4 .

[0043] The second flame retardant is a liquid-phase monomer of acrylate containing fluorine element, and its content accounts for 1-4 wt% of the total mass of the electrolyte. The structural general formula of the monomer is shown as Formula II below:

[0044]

[0045] In formula II: R 3 , R 4 are each independently selected from -F, -OH, -CF 3 , C 1 -C 4 alkoxy groups, C 2 -C 6 heterocyclic alkoxy groups containing at least one oxygen atom as a ring-forming atom, phenyl, and C 1 -C 4 alkyl groups, one of them.

[0046] The cross-linking agent is a liquid-phase monomer containing one or more acrylate functional groups, and its content accounts for 1-2 wt% of the total mass of the electrolyte. Its structural general formula is shown as formula III below:

[0047]

[0048] In formula III: R 5 , R 6 , R 7 are each independently selected from -OH, -C 3 H 3 O 2 , C 1 -C 4 alkoxy groups, C 2 -C 6 heterocyclic alkoxy groups containing at least one oxygen atom as a ring-forming atom, phenyl, nitro, and methylsulfonyl groups, one of them.

[0049] The initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, dimethyl azobisisobutyrate, 2,2-azobisisobutyronitrile, ammonium persulfate-sodium bisulfite, and its content accounts for 0.05-1 wt% of the total mass of the electrolyte.

[0050] In addition to the above components in the gel polymer electrolyte, the balance is a liquid electrolyte. The liquid electrolyte includes a solvent and a lithium salt; the solvent is one or more combinations of ethylene carbonate (EC), dimethyl carbonate, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), vinylene carbonate, fluoroethylene carbonate (FEC), divinyl sulfite (DTD), propylene carbonate, propane sultone (PS), tris(trimethylsilyl) phosphate (TMSP); the lithium salt is one or more of lithium perchlorate, lithium tetrafluoroborate, lithium difluorophosphate, lithium hexafluorophosphate (LiPF 6 ), lithium difluorooxalate borate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide (LiFSI).

[0051] A preparation method of a flame-retardant gel polymer battery uses the above-mentioned multi-effect flame-retardant in-situ gel polymer electrolyte as a raw material, and the specific steps are as follows:

[0052] (1) Under an inert gas atmosphere, the first flame retardant, crosslinking agent, initiator and liquid electrolyte are fully mixed in the above proportion to obtain electrolyte precursor A.

[0053] (2) Under an inert gas atmosphere, the second flame retardant, crosslinking agent, initiator and liquid electrolyte are fully mixed in the above proportion to obtain electrolyte precursor B.

[0054] (3) Prepare a dry battery cell with ternary material / lithium iron phosphate as the positive electrode and graphite as the negative electrode.

[0055] (4) Inject electrolyte precursor B into the dry battery cell. After the electrolyte precursor B is evenly infiltrated, formation is carried out at 45-60 °C, and the formation current is 0.05C-0.2C. Then aging is carried out at 45-60 °C for 24-48 h.

[0056] (5) Inject electrolyte precursor A into the treated battery cell. After standing evenly, high-temperature polymerization is carried out at 60-80 °C for 4-8 h to obtain a flame-retardant gel polymer battery.

[0057] Example 1

[0058] A preparation method of a flame-retardant gel polymer battery, the specific steps are as follows:

[0059] (1) Under an inert gas atmosphere, the first flame retardant (diethyl vinyl phosphate), crosslinking agent (pentaerythritol triacrylate), initiator (azobisisobutyronitrile) and liquid electrolyte (EC, EMC, DEC, LiPF with a mass ratio of 24:16:40:9:2.4:3:3:1:0.6:1 6 , LiFSI, LiDFOB, FEC, DTD, PS, TMSP) are fully mixed to obtain electrolyte precursor A.

[0060] (2) Under an inert gas atmosphere, the second flame retardant (hexafluorobutyl acrylate), crosslinking agent (pentaerythritol triacrylate), initiator (azobisisobutyronitrile) and liquid electrolyte (EC, EMC, DEC, LiPF with a mass ratio of 24:16:40:9:2.4:3:3:1:0.6:1 6 , LiFSI, LiDFOB, FEC, DTD, PS, TMSP) are fully mixed to obtain electrolyte precursor B.

[0061] (3) Prepare a dry battery cell with ternary material (LiNi8 Co 1 Mn 1 O 2 ) is used as the positive electrode and graphite is used as the negative electrode.

[0062] (4) Inject electrolyte precursor B (accounting for 80% of the total electrolyte content) into the dry battery cell. After the electrolyte precursor B is evenly infiltrated, formation is carried out at 45 °C with a formation current of 0.05C, and then aging is carried out at 45 °C for 48h.

[0063] (5) Inject electrolyte precursor A (accounting for 20% of the total electrolyte content) into the treated battery cell. After standing evenly, high-temperature polymerization is carried out at 60 °C for 4h to obtain a flame-retardant gel polymer battery.

[0064] Example 2

[0065] A method for preparing a flame-retardant gel polymer battery, the specific steps are as follows:

[0066] (1) Under an inert gas atmosphere, the first flame retardant (diethyl vinyl phosphate), crosslinking agent (pentaerythritol triacrylate), initiator (benzoyl peroxide), and liquid electrolyte (EC, EMC, DEC, LiPF with a mass ratio of 24:16:40:9:2.4:3:3:1:0.6:1 6 , LiFSI, LiDFOB, FEC, DTD, PS, TMSP) are fully mixed to obtain electrolyte precursor A.

[0067] (2) Under an inert gas atmosphere, the second flame retardant (hexafluorobutyl acrylate), crosslinking agent (pentaerythritol triacrylate), initiator (benzoyl peroxide), and liquid electrolyte (EC, EMC, DEC, LiPF with a mass ratio of 24:16:40:9:2.4:3:3:1:0.6:1 6 , LiFSI, LiDFOB, FEC, DTD, PS, TMSP) are fully mixed to obtain electrolyte precursor B.

[0068] (3) Prepare a dry battery cell, using a ternary material (LiNi 8 Co 1 Mn 1 O 2 ) as the positive electrode and graphite as the negative electrode.

[0069] (4) Inject electrolyte precursor B (accounting for 80% of the total electrolyte content) into the dry battery cell. After the electrolyte precursor B is evenly infiltrated, formation is carried out at 45 °C with a formation current of 0.05C, and then aging is carried out at 45 °C for 48h.

[0070] (5) The electrolyte precursor A (accounting for 20% of the total electrolyte content) was injected into the treated battery cell, and after standing evenly, high-temperature polymerization was carried out at 60° C. for 4 hours to obtain a flame-retardant gel polymer battery.

[0071] Example 3

[0072] A method for preparing a flame retardant gel polymer battery, the specific steps are as follows:

[0073] (1) In an inert gas atmosphere, a first flame retardant (tri(acryloyloxyethyl) phosphate), a crosslinking agent (pentaerythritol triacrylate), an initiator (azobisisobutyronitrile) and a liquid electrolyte (EC, EMC, DEC, LiPF in a mass ratio of 24:16:40:9:2.4:3:3:1:0.6:1) were mixed at a ratio of 1:1:0.05:97.95. 6 , LiFSI, LiDFOB, FEC, DTD, PS, TMSP) are fully mixed to obtain electrolyte precursor A.

[0074] (2) Under an inert gas atmosphere, a second flame retardant (hexafluorobutyl acrylate), a crosslinking agent (pentaerythritol triacrylate), an initiator (azobisisobutyronitrile) and a liquid electrolyte (EC, EMC, DEC, LiPF in a mass ratio of 24:16:40:9:2.4:3:3:1:0.6:1) were mixed at a ratio of 2:1:0.05:96.95. 6 , LiFSI, LiDFOB, FEC, DTD, PS, TMSP) are fully mixed to obtain electrolyte precursor B.

[0075] (3) Preparation of dry cells using lithium iron phosphate (LiFePO 4 ) is the positive electrode and graphite is the negative electrode.

[0076] (4) Inject electrolyte precursor B (accounting for 80% of the total electrolyte content) into the dry battery cell. After the electrolyte precursor B is evenly infiltrated, it is formed at 45°C with a forming current of 0.05C, and then aged at 45°C for 48 hours.

[0077] (5) The electrolyte precursor A (accounting for 20% of the total electrolyte content) was injected into the treated battery cell, and after standing evenly, high-temperature polymerization was carried out at 60° C. for 4 hours to obtain a flame-retardant gel polymer battery.

[0078] Example 4

[0079] A method for preparing a flame retardant gel polymer battery, the specific steps are as follows:

[0080] (1) Under an inert gas atmosphere, the first flame retardant (diphenyl octyl phosphate), crosslinking agent (pentaerythritol triacrylate), initiator (azobisisobutyronitrile), and liquid electrolyte (EC, EMC, DEC, LiPF with a mass ratio of 24:16:40:9:2.4:3:3:1:0.6:1 6 , LiFSI, LiDFOB, FEC, DTD, PS, TMSP) were fully mixed to obtain electrolyte precursor A.

[0081] (2) Under an inert gas atmosphere, the second flame retardant (hexafluorobutyl acrylate), crosslinking agent (pentaerythritol triacrylate), initiator (azobisisobutyronitrile), and liquid electrolyte (EC, EMC, DEC, LiPF with a mass ratio of 24:16:40:9:2.4:3:3:1:0.6:1 6 , LiFSI, LiDFOB, FEC, DTD, PS, TMSP) were fully mixed to obtain electrolyte precursor B.

[0082] (3) Prepare a dry battery cell with a ternary material (LiNi 8 Co 1 Mn 1 O 2 ) as the positive electrode and graphite as the negative electrode.

[0083] (4) Inject electrolyte precursor B (accounting for 80% of the total electrolyte content) into the dry battery cell. After the electrolyte precursor B is evenly infiltrated, formation is carried out at 45 °C with a formation current of 0.05C, and then aging is carried out at 45 °C for 48 h.

[0084] (5) Inject electrolyte precursor A (accounting for 20% of the total electrolyte content) into the treated battery cell. After standing evenly, high-temperature polymerization is carried out at 60 °C for 4 h to obtain a flame-retardant gel polymer battery.

[0085] Comparative Example 1

[0086] A method for preparing a gel polymer battery, the specific steps are as follows:

[0087] (1) Under an inert gas atmosphere, the flame retardant monomer (triethyl phosphate), crosslinking agent (pentaerythritol triacrylate), initiator (azobisisobutyronitrile), and liquid electrolyte (EC, EMC, DEC, LiPF with a mass ratio of 24:16:40:9:2.4:3:3:1:0.6:1 6 , LiFSI, LiDFOB, FEC, DTD, PS, TMSP) were fully mixed to obtain an electrolyte precursor.

[0088] (2) Prepare a dry battery cell using ternary material (LiNi 8 Co 1 Mn 1 O 2 ) as the positive electrode and graphite as the negative electrode.

[0089] (3) Inject the electrolyte precursor into the dry battery cell. After the electrolyte precursor is evenly infiltrated, perform formation at 45°C with a formation current of 0.05C, and then age at 45°C for 48 hours to obtain a polymer battery.

[0090] Test Example 1

[0091] 1. Electrochemical performance test

[0092] Perform cycle performance, needle penetration test, and hot box test on the batteries prepared in Examples 1-4 and Comparative Example 1. Among them, the cycle test is carried out at room temperature of 25°C, the charge-discharge rate is 0.5C, the charge-discharge regime is constant current-constant voltage charging and constant current discharging, and the test voltage range is 2.7-4.2V; the needle penetration test is carried out according to the national standard GB / T 31485-2015. The test results are shown in Table 1 below.

[0093] Table 1 Electrochemical performance test

[0094]

[0095]

[0096] 2. Flame retardancy performance test

[0097] Polymerize the electrolyte precursors prepared in Examples 1-4 and Comparative Example 1 in a sample bottle, expose the obtained electrolyte to an open flame, and detect its flame retardancy performance. The test results are shown in Table 2 below.

[0098] Table 2 Flame retardancy performance

[0099] Case Combustion situation after contacting the flame for 10s Example 1 Non-combustible Example 2 Non-combustible Example 3 Non-combustible Example 4 Non-combustible Comparative example 1 Flammable

[0100] 3. Result analysis

[0101] It can be seen from the test results in Table 1 and Table 2 that the multi-effect flame-retardant in-situ gel polymer electrolyte (GPE) prepared in the present invention is significantly superior to Comparative Example 1 (traditional GPE) in terms of flame retardancy performance and electrochemical performance. The specific analysis is as follows:

[0102] (1) Electrochemical performance

[0103] The data in Table 1 show that the internal resistance of the batteries prepared in Examples 1-4 is lower than that in Comparative Example 1. Among them, the internal resistance of Example 1 is the lowest, which is 6.63 mΩ, the internal resistance of Example 4 is 6.87 mΩ, and the internal resistance of Comparative Example 1 is 6.91 mΩ. This shows that the present invention promotes the dissociation of lithium salts by introducing fluorine elements, reduces the internal resistance of the battery, and thus improves the power performance of the battery.

[0104] In terms of battery capacity, the capacities of Examples 1-4 are similar to those of Comparative Example 1. Among them, Example 1 has the highest capacity, which is 5.13 Ah, while the capacity of Example 4 is 5.04 Ah, and the capacity of Comparative Example 1 is 5.04 Ah. This shows that the present invention improves the flame retardant performance without sacrificing the capacity performance of the battery.

[0105] In terms of the capacity retention rate after 1000 cycles of the battery, Examples 1-4 are all better than Comparative Example 1. Among them, Example 1 has the highest capacity retention rate of 82%, Example 4 has a capacity retention rate of 75%, and Comparative Example 1 has a capacity retention rate of only 74%. This result shows that the present invention avoids the decomposition of the phosphorus flame retardant by fixing the flame retardant in the polymer matrix, and the introduction of fluorine element increases the lithium ion migration number, thereby significantly improving the cycle stability of the battery.

[0106] In the needle puncture test, Examples 1-4 all passed the test, showing good safety performance. In contrast, Comparative Example 1 failed the needle puncture test. This shows that the present invention fixes the electrolyte through a three-dimensional network structure, effectively inhibits the leakage and volatilization of the electrolyte, and further improves the intrinsic safety of the battery.

[0107] (2) Flame retardant properties

[0108] According to the data in Table 2, the electrolytes prepared in Examples 1-4 did not burn after contacting the fire source for 10 seconds, showing excellent flame retardant properties. In contrast, the electrolyte in Comparative Example 1 burned under the same conditions. This result shows that the present invention significantly improves the flame retardant properties of the electrolyte by fixing the flame retardant in the polymer matrix and introducing phosphorus- and fluorine-containing dual flame retardants. Among them, the phosphorus-based flame retardant plays a flame retardant role in the solid phase, and the F radicals released by the fluorine-based flame retardant during the combustion process can volatilize into the gas phase, remove H radicals, and inhibit chain combustion reactions, thereby achieving dual flame retardant effects in the gas phase and the solid phase.

[0109] (3) Comprehensive performance comparison

[0110] Examples 1-4 are significantly better than Comparative Example 1 in terms of flame retardancy, battery internal resistance, cycle performance and safety performance. In particular, in terms of flame retardancy and cycle performance, the present invention achieves a balance between flame retardancy and electrochemical performance through the synergistic effect of phosphorus- and fluorine-containing dual flame retardants and the immobilization design of the flame retardants.

[0111] In Comparative Example 1, due to the lack of the flame retardant immobilization design and the synergistic effect of the fluorine-based flame retardant, its flame retardant performance is poor, and the flame retardant decomposes during the cycle, affecting the electrochemical performance and safety performance of the battery.

[0112] In summary, the in-situ gel polymer electrolyte with multi-effect flame retardancy of the present invention not only significantly improves the flame retardant performance of the electrolyte by fixing the flame retardant in the polymer matrix and introducing a phosphorus- and fluorine-containing double flame retardant, but also improves the electrochemical performance and safety performance of the battery by optimizing the lithium ion transference number and inhibiting the decomposition of the flame retardant. The test results show that the present invention is superior to the traditional GPE (Comparative Example 1) in terms of battery internal resistance, capacity retention rate, cycle performance and safety performance, providing an effective solution for the development of high-safety and high-performance lithium ion batteries.

[0113] The embodiments described above are only a part of the embodiments of the present invention, rather than all embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. The protection scope of the present invention shall be subject to the scope claimed in the claims. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

Claims

1. A multi-effect flame-retardant in-situ gel polymer electrolyte, characterized in that: The electrolyte is a gel polymer electrolyte with a three-dimensional network structure prepared in situ by a first flame retardant, a second flame retardant, a crosslinking agent, an initiator and a liquid electrolyte; the first flame retardant is an acrylate liquid monomer containing phosphorus, and its content accounts for 1 to 4 wt% of the total mass of the electrolyte; the second flame retardant is an acrylate liquid monomer containing fluorine, and its content accounts for 1 to 4 wt% of the total mass of the electrolyte; the content of the crosslinking agent accounts for 1 to 2 wt% of the total mass of the electrolyte; the content of the initiator accounts for 0.05 to 1 wt% of the total mass of the electrolyte; and the balance is liquid electrolyte.

2. The multi-effect flame-retardant in-situ gel polymer electrolyte according to claim 1, characterized in that: The general structural formula of the monomer of the first flame retardant is shown in Formula I below: In formula I: R1 and R2 are each independently selected from one of a C1-C4 alkoxy group, a C2-C6 heterocycloalkoxy group containing at least one oxygen atom as a ring atom, a phenyl group, a C1-C4 alkanoyl group, a nitro group, a methylsulfonyl group, a C1-C4 sulfonic acid group and a C1-C4 alkyl group.

3. The multi-effect flame-retardant in-situ gel polymer electrolyte according to claim 1, characterized in that: The general structural formula of the monomer of the second flame retardant is shown in Formula II below: In formula II: R3 and R4 are each independently selected from one of -F, -OH, -CF3, C1-C4 alkoxy, C2-C6 heterocycloalkoxy containing at least one oxygen atom as a ring atom, phenyl and C1-C4 alkyl.

4. The multi-effect flame-retardant in-situ gel polymer electrolyte according to claim 1, characterized in that: The crosslinking agent is a liquid phase monomer containing one or more acrylate functional groups, and its general structural formula is shown in the following formula III: In formula III: R5, R6, and R7 are each independently selected from one of -OH, -C3H3O2, a C1-C4 alkoxy group, a C2-C6 heterocycloalkoxy group containing at least one oxygen atom as a ring atom, a phenyl group, a nitro group, and a methylsulfonyl group.

5. The multi-effect flame-retardant in-situ gel polymer electrolyte according to claim 1, characterized in that: The initiator is one or more of azobisisobutyronitrile, dibenzoyl peroxide, dimethyl azobisisobutyrate, 2,2-azobisisobutyronitrile, and ammonium persulfate-sodium bisulfite.

6. The multi-effect flame-retardant in-situ gel polymer electrolyte according to claim 1, characterized in that: The liquid electrolyte comprises a solvent and a lithium salt; the solvent is a combination of one or more of ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, propylene carbonate, propane sultone, and tris(trimethylsilyl)phosphate; the lithium salt is one or more of lithium perchlorate, lithium tetrafluoroborate, lithium difluorophosphate, lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl imide), and lithium bis(fluorosulfonyl imide).

7. Use of the multi-effect flame-retardant in-situ gel polymer electrolyte according to any one of claims 1 to 6 in the preparation of lithium-ion batteries.

8. The use according to claim 7, characterized in that: The preparation method of a lithium-ion battery comprises the following steps: Step 1) In an inert gas atmosphere, a first flame retardant, a crosslinking agent, an initiator and a liquid electrolyte are fully mixed in proportion to obtain an electrolyte precursor A; Step 2) In an inert gas atmosphere, the second flame retardant, the crosslinking agent, the initiator and the liquid electrolyte are fully mixed in proportion to obtain an electrolyte precursor B; Step 3) preparing a dry battery cell; Step 4) injecting electrolyte precursor B into the dry battery cell, and performing formation and aging after the electrolyte precursor B is evenly infiltrated; Step 5) injecting the electrolyte precursor A into the battery cell treated in step 4), allowing it to stand evenly and then polymerizing it at high temperature to obtain a flame retardant gel polymer battery.

9. The use according to claim 8, characterized in that: Step 4) The formation temperature is 45-60° C., and the formation current is 0.05C-0.2C; the aging temperature is 45-60° C., and the aging time is 24-48 hours.

10. The use according to claim 8, characterized in that: Step 5) The temperature of the high temperature polymerization is 60-80°C and the time is 4-8h.

Citation Information

Patent Citations

  • Preparation method of flame-retardant lithium ion battery gel electrolyte

    CN113234195A

  • Gel electrolyte composition and preparation method thereof, gel electrolyte and preparation method and application of gel electrolyte

    CN113717328A

  • High-safety semi-solid lithium ion battery and preparation method thereof

    CN118336128A

  • Flame-retardant gel electrolyte, preparation method thereof and semi-solid lithium metal battery

    CN118867366A

  • Semi-solid sodium ion battery and preparation method thereof

    CN119400947A

Cited By

  • Gel electrolyte precursor, gel electrolyte, secondary battery and method

    CN121405853A

  • High-safety quasi-solid gel electrolyte, preparation method and application

    CN121839866A

  • High-safety flame-retardant gel electrolyte, preparation method thereof and lithium ion battery

    CN122552620A